Appointment with F.E.A.R. (Fighting Fantasy) - Steve Jackson (London Wizard Books, 2011)
Fighting Fantasy is the brilliant series of adventure games where YOU are the hero. Your mission is to discover the location of the top- secret F.E.A.R. meeting, capture the Titanium Cyborg and his cohorts bring them to justice. Ages violence, kidnapping and corruption of a host of super-villans.